Impact of Halal Tourism on Revisit Intention: The Role of Homophily at Sabang Island - Mega Hernawati Harefa; Tina Linda; Lidia Berliana Siboro; Jimmy Kelana; Tony Honkley (Journal of Business Integration Competitive, 2026)
This study examines the impact of halal tourism on return intention, with homophily as a mediating variable among visitors from North Sumatra who travel to tourist destinations in Sabang Island and Banda Aceh. The growing interest in halal tourism highlights the importance of aligning tourism services with travelers' religious beliefs. However, there remains a gap in understanding how perceived social and cultural similarities (homophily) can enhance revisit intention. A quantitative approach was used, employing a survey technique to collect data from 95 respondents through accidental sampling. Structural Equation Modeling Partial Least Squares (SEM-PLS) was applied to assess direct and indirect relationships between variables. The findings show that halal tourism positively and significantly impacts revisit intention. Additionally, halal tourism significantly influences homophily, which, in turn, affects revisit intention. These results suggest that homophily mediates the relationship between halal tourism and return intention. When tourists share similar beliefs, lifestyles, and religious practices with a destination, it fosters emotional connection and comfort. This study emphasizes the importance of developing halal tourism locations that not only provide sharia-compliant facilities but also cultivate social interactions tailored to tourists' attributes. Destination managers and stakeholders must focus on value alignment, community engagement, and inclusive social interactions to enhance tourist loyalty and encourage repeat visits